A Review of Virtual Reality Applications in an Educational Domain - Al Farsi G.; bin Mohd. Yusof A.; Romli A.; Tawafak R.M.; Malik S.I.; Jabbar J.; Bin Rsuli M.E. (International Association of Online Engineering, 2023)
The use of virtual reality (VR) applications has grown tremendously in recent years. This paper focuses on the review of existing virtual reality applications in higher educational institutions. The VR applications are still not widely used although it helps students learn and enhances their performance. Moreover, some factors that lead to the limited use of virtual reality are lack of communication, delay in technology development, weak acquisition of knowledge, etc. This paper provides a comprehensive overview of virtual reality applications in educational institutions. The reviewed articles are taken from databases such as Science Direct, Ebscohost, and Scopus. Furthermore, the reviewed eighteen articles are published between 2016 and 2021. The study analyzed the reviewed articles based on different factors such as fields, purpose, targets, methods, citations, factors, and limitations. The findings revealed that virtual reality applications could play an essential role in the education domain. The reviewed articles highlighted the significant contribution of virtual reality applications in the education domain and their impact on the students performance. Moreover, the study revealed the critical factors used in VR environments, such as ease of use, efficiency, interactive environments, effectiveness, and learning environments. 2021. All Rights Reserved.